Why shrinking cities are not mirror images of growing cities: a research agenda of six testable propositions - Galster, George (2019)
I advance six propositions regarding the features of urban decline processes that distinguish them from those in growing cities. First, they are demographically selective, as population losses are disproportionately comprised of more advantaged households. Second, they are dynamically nonlinear, as population changes exceed thresholds where socially problematic behaviors and residential disinvestment jump sharply. Third, they are asymmetrically scalable for technological, financial, physical, and political reasons. Fourth, they are minimally controlled by traditional land-use policies of zoning and building permits. Fifth, they are informally decentralized, as individuals and groups supplement the atrophied local public sector with (3z(Bdo it yourself(3y (Bactivities. Sixth, they are psychologically conservative, as residents try to conserve threatened physical, social, and psychological resources. The article synthesizes extant theory and evidence from multiple disciplines, although ultimately the propositions are advanced as working hypotheses commanding varying degrees of support, which collectively comprise a research agenda for further investigation. - Reproduced.s
Keywords: Urban areas